Prediction of the Time Spent on Instagram by Social Media Addiction and Life Satisfaction - Yeşilyurt, Ferahim; Turhan, Nihan Sölpük (Birleşik Dünya Yenilik Araştırma ve Yayıncılık Merkezi, 2020)
There are many different debates regarding the time spent on Instagram by social media addiction and life satisfaction. In consequence, in this research, it is aimed to reveal the variables that predict the time spent on Instagram by university students. The research is done in accordance with the causal and correlation model by using a quantitative research method. The results of the research are predicted by the time spent on Instagram, gender, age and social media addiction. Time spent on Instagram differentiates in accordance with the level of social media addiction (Sig = 0.00, p < 0.05) but does not differentiate by life satisfaction (Sig = 0.06, p > 0.05). As social media addiction increases, life satisfaction decreases (r = −0.19). Women spent 0.42 times more time, and the women at the age of 21–22 years spent 0.38 times more time on Instagram.
Keywords: Instagram; Life Satisfaction; Social Media; Addiction